2010
DOI: 10.1111/j.1477-2574.2009.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of randomized controlled trials of pharmacological interventions to reduce ischaemia-reperfusion injury in elective liver resection with vascular occlusion

Abstract: Methylprednisolone, trimetazidine, dextrose and ulinastatin may have protective roles against IR injury in liver resection. However, based on the current evidence, they cannot be recommended for routine use and their application should be restricted to RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
0
30
0
2
Order By: Relevance
“…Improved liver function markers and/or reduced liver injury markers indicated that methylprednisolone, trimetazidine, dextrose and ulinastatin could have possible protective effects against IRI in vascular controlled liver resections [4] . However, literature shows no significant differences in mortality, liver failure or peri-or postoperative mortality for any pharmacological intervention [4,65] . Hence, based on current evidence, it cannot be advised to administer medication with the purpose of limiting IRI in vascular controlled liver resection [65] .…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved liver function markers and/or reduced liver injury markers indicated that methylprednisolone, trimetazidine, dextrose and ulinastatin could have possible protective effects against IRI in vascular controlled liver resections [4] . However, literature shows no significant differences in mortality, liver failure or peri-or postoperative mortality for any pharmacological intervention [4,65] . Hence, based on current evidence, it cannot be advised to administer medication with the purpose of limiting IRI in vascular controlled liver resection [65] .…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…However, literature shows no significant differences in mortality, liver failure or peri-or postoperative mortality for any pharmacological intervention [4,65] . Hence, based on current evidence, it cannot be advised to administer medication with the purpose of limiting IRI in vascular controlled liver resection [65] . The use of these drugs should only be used in well-designed clinical trials before clinical implementation [4,62,63] .…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Furthermore, the liver function of the experimental group was significantly better than that of the control group the first and fifth day after the operation. As far as ulinastatin is concerned, although it lowered the transaminase and bilirubin levels, it did not affect the rates of liver decompensation, perioperative morbidity or length of hospital stay (57,61). Based on these results, it seems that ulinastatin may offer a protective role in elective liver resections under vascular occlusion.…”
Section: Other Promising Pharmacological Interventionsmentioning
confidence: 99%
“…Aufgrund fehlender valider Daten kann aber bisher keine pharmakologische Strategie für die Routinetherapie empfohlen werden [43,45]. [46,47].…”
Section: Disclosure Statementunclassified